Antibacterial mechanism of action and in silico molecular docking studies of Cupressus funebris essential oil against drug resistant bacterial strains - Caixin Yuan; Xiuqiao Hao (Heliyon, 2023)
The primary objective of this research work was to study the antibacterial effects of Cupressus funebris essential oil (EO) against various drug resistant bacterial pathogens along with studying the molecular docking interactions of the major components of the EO with the key bacterial proteins/enzymes. Gas chromatography-mass spectrometry was used to analyse the chemical composition of the Cupressus funebris EO. The initial antibacterial screening was performed by using disc diffusion and microdilution methods. Scanning electron microscopy was also performed in order to study effects of the EO on bacterial cell morphology. Further, molecular docking studies were performed using Autodock Vina and results were visualised by BIOVIA Discovery Studio. The chemical composition of the EO showed the presence of 15 components with citronellal, terpinene-4-ol, α-phellandrene and 1,8-cineole as the major components of the EO. Results indicated that the EO of Cupressus funebris exhibited dose-dependent as well as time dependent antibacterial effects. The scanning electron microscopy indicated that the Cupressus funebris EO led to membrane rupture and permeabilization of the bacterial cells. Molecular docking studies indicated that the major compounds of the EO (citronellal and terpinene-4ol) showed strong interactions with the active site of the bacterial DNA gyrase enzyme explaining the antibacterial mode of action of the EO. Ciprofloxacin was also used for docking which showed stronger interactions with the target protein than citronellal or terpinene-4-ol. In conclusion, the major findings of the current study were that the EO of Cupressus funebris causes bacterial membrane rupture and permeabilization, shows time-dependent and dose-dependent antibacterial action, along with interacting with crucial bacterial enzyme viz., DNA gyrase as indicated by molecular docking studies.